New Advances in Environmental Friendly Materials - Garcia, Nancy Lis (2018)
This last decade has been characterized by the acquisition ofnew materials based on the biomass, with the objective of replacingthe materials obtained from petroleum derivatives, due to the highcosts, added to the fact that they are non-renewable inputs and as ameasure of the preservation of the environment [1]. In all areas ofstudy has been this responsibility of searching for new and versatilematerials. Packaging, medical materials, agro-industry, cosmetics,even energy applications, in all these fields are in constant search tobe at the forefront and at the same time reduce all those materialsthat, during and at the end of their life cycle, cause damage to theenvironment, either due to the emission of greenhouse gases, orbecause they lack biodegradable and / or compostable properties